Respiratory syncytial virus vaccination among US adults aged ≥60 years - Geng, Xiaozhen; Wang, Wenjun (Frontiers in Immunology, 2024)
BackgroundRespiratory syncytial virus (RSV) vaccines have been recommended for US adults aged ≥60 years for nearly one year. However, the extent of vaccination coverage and the factors influencing uptake remain underexplored. This study aimed to evaluate national and state-specific RSV vaccination coverage among US adults aged ≥60 years and to identify demographic and socioeconomic factors that influence vaccination uptake.MethodsThis cross-sectional study analyzed data from the US Census Household Pulse Survey, from January 9 to March 4, 2024, which included 49,322 adults aged ≥60 years. Participants self-reported their RSV vaccination status along with demographic and socioeconomic information. Multivariable Poisson regression was used to identify factors associated with vaccination uptake.ResultsAs of March 4, 2024, RSV vaccination coverage among US adults aged ≥60 years was estimated at 22.2% (95% CI, 21.6%-22.7%). State-specific vaccination coverage ranged from 12.4% in Mississippi to 33.1% in Colorado. Coverage was higher in older age groups, with 21.2% among those aged 65-69 years, 28.1% among 70-74 years, 31.9% among 75-79 years, and 30.2% among those aged ≥80 years, compared to 10.8% among those aged 60-64 years. Racial/ethnicity disparities were evident, with lower coverage among Hispanics (18.3%) and non-Hispanic Blacks (17.6%) compared to non-Hispanic Whites (23.3%). Coverage was similar between males (22.6%) and females (21.8%). Factors positively associated with vaccination included older age, higher education level, higher household income, unemployment, and residing in the Midwest or West. Conversely, being non-Hispanic Black, uninsured, experiencing financial difficulties, and lack of COVID-19 vaccination were associated with reduced likelihood of receiving the RSV vaccine.ConclusionsDuring the first RSV season after the recommendations for RSV vaccination in US adults aged ≥60 years, uptake shows promise but is marked by significant disparities related to race/ethnicity, socioeconomic status, and geographic location. Efforts to address these disparities are crucial to enhance vaccination coverage and reduce the impact of RSV on this vulnerable population.